Differences in food intake, body composition, and physical activity between university students with normal - weight obesity and normal - weight lean - Hariyanto, Agus; Mautang, Theo Welly Evert; Usman, Arifuddin; Akhmad, Imran; Hartati, Hartati; Nasuka, Nasuka; Sholikhah, Anindya Mar´ atus (O Mundo da Saúde, 2025)
Normal-weight obesity (NWO) is a prevalent health issue characterized by a normal Body Mass Index (BMI) alongside a high body fat percentage (BF%). An unhealthy lifestyle, characterized by poor quality of food intake and lack of physical activity, is a contributing factor to NWO. This study aims to investigate the differences in healthy food intake, physical activity, and body composition parameters between students identified as NWO and normal‑weight lean (NWL). This was a cross-sectional study involving 149 university students. Body composition measurements were carried out using the InBody 370s. Physical activity data were measured using the General Physical Activity Questionnaire, and food intake quality was collected using the Food Frequency and Recommended Food Score (RFS). Comparative tests were applied to assess differences in measured variables between groups. Among the participants, 31.5% were classified as NWO, 49.7% engaged in moderate physical activity, and only 27.52% adhered to a healthy diet. Furthermore, we found lower physical activity (PA) scores and healthy food intake in NWO students compared to NWL group. Significant differences were also observed in body composition parameters, where BMI, PBF, fat-mass, fat-free mass, and BMR were higher in students with normal weight (p<0.05). This study highlights the urgent need for interventions aimed at promoting healthy lifestyles, which can help students achieve and maintain a balanced body composition. By focusing on enhancing physical activity levels and improving dietary intake, it is possible to mitigate the risks associated with NWO and achieve better health outcomes. Thus, the findings suggest that universities should implement targeted wellness programs, such as nutrition education, campus fitness initiatives, and accessible wellness resources, to encourage sustainable lifestyle changes. These measures can help prevent obesity-related health problems and improve students’ overall well-being and academic performance.